Sistem Penataan Kawasan Stasiun Kota Bekasi Sebagai Upaya Mengatasi Kemacetan Lalu Lintas - Yudo Hariyanto; Irwan Prasetyo; Zefri Zefri (Jurnal Kajian Wilayah dan Kota, 2022)
Land Stewardship Balance is the balance between the availability of land and the need for control, use and utilization of land according to the function of the Regional Spatial Plan (RTRW) area. The meaning shows that the existence of this balance sheet can be an important element in the preparation of the Detailed Spatial Plan (RDTR) or Zoning Regulation (PZ). The research objective is to prepare a spatial pattern balance sheet as a strategy to control space utilization in accordance with the Bekasi Regency spatial plan. In this study, it can be seen that in the conversion of the Bekasi Regency spatial pattern, there is an additional area of 55,125.57 Ha of Bekasi Regency with a reduction of 74,136.29 Ha. The largest area addition occurred in wetland agricultural allotments. There are eighteen sources of land use that increase the area of wetland agriculture (wetland agriculture appears in eighteen of these land uses). While the largest source of reduction is on land allocation for settlements, which amounted to 27,299.23 hectares. Based on the results of the analysis and preparation of the land availability balance, it is known that the available land area in Bekasi Regency is 65,055.10 Ha, while the unavailable land area in Bekasi Regency is 61,793.17 Ha